Participation in disability benefit programmes: a partial identification analysis of the British Attendance Allowance system - Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2009)
We investigate the processes underlying payment of Attendance Allowance (AA) in the older UK population, using a partial identication approach. Receipt of AA requires that (i) a claim is made and (ii) programme administrators assess the claim as warranting an award. These processes cannot be analysed directly because we observe neither potentially successful unpursued claims, nor rejected claims. Combining survey data with weak prior restrictions and aggregate information on claim success rates, we are able to distinguish clearly the behaviour of potential claimants and assessors. Results suggest that there are many potentially successful AA claims which are not pursued.
Keywords: 330